2005
DOI: 10.1677/erc.1.00960
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability predicts metastatic disease in patients with insulinomas

Abstract: Endocrine pancreatic tumors (EPTs) comprise a highly heterogeneous group of tumors with different clinical behavior and genetic makeup. Insulinomas represent the predominant syndromic subtype of EPTs. The metastatic potential of insulinomas can frequently not be predicted using histopathological criteria, and also molecular markers indicating malignant progression are unreliable because of the small number of cases per subtype studied so far. For the identification of reliable indicators of metastatic disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 52 publications
7
56
1
Order By: Relevance
“…This may be due to the fact that not all deletions are picked up in CGH analysis due to its limitations in resolution. 23 The observed loss rate of 45% is in accordance with our previous work, where we found 31% loss in a series of 29 pheochromocytomas, and with LOH analyses performed by others, which showed loss rates between 18 and 24%. 5,18,27 In five pheochromocytomas (10%), gain of 17p was found in CGH, although copy number gain could only be confirmed in two instances by FISH analysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to the fact that not all deletions are picked up in CGH analysis due to its limitations in resolution. 23 The observed loss rate of 45% is in accordance with our previous work, where we found 31% loss in a series of 29 pheochromocytomas, and with LOH analyses performed by others, which showed loss rates between 18 and 24%. 5,18,27 In five pheochromocytomas (10%), gain of 17p was found in CGH, although copy number gain could only be confirmed in two instances by FISH analysis.…”
Section: Discussionsupporting
confidence: 92%
“…23 This approach uses differentially labelled tumor and 'reference' DNA, which are competitively hybridized to normal metaphase chromosomes. The ratio of the fluorescence intensities detected is indicative of the relative DNA copy number in tumor vs reference DNA.…”
Section: Cghmentioning
confidence: 99%
See 1 more Smart Citation
“…In metastasized ATC, the number of gains remains stable, while a significant increase of genomic losses is seen (Figure 1), indicating that loss of function mutations are involved in the process of tumor dissemination. For pancreatic endocrine neoplasms, similar observations concerning an increase of CIN in metastasized versus non-metastasized tumors were previously reported (Jonkers et al, 2005) Our data suggest a model of carcinoid development and progression in which mitotic infidelity causes CIN at an early stage. During tumor progression, especially chromosomal losses inactivate the functions of tumor suppressor genes and promote metastatic behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…Deletion 6q was associated with metastasis in insulinoma (42), and deletions 6q14 and 6q16-q23 have been reported as recurrent cytogenetic aberrations in OS (43,44). Likewise, previous studies have shown an association of deletion 8p with disease progression in hepatocellular carcinoma (45) and colon cancer (46).…”
Section: Discussionmentioning
confidence: 87%